THE INFLUENCE OF OURTOGA WEBSITE-BASED GREEN MARKETING ON ASSESSEES' INTEREST IN THE INDONESIAN PROFESSIONAL ENVIRONMENTAL CERTIFICATION INSTITUTE - Sakha Nurwitono, Dary; Pradana, Mahir; Winarno, Alex (Fakultas Pendidikan Ekonomi dan Bisnis, 2023)
Professional Certification is the process of providing competency certificates for certain professions/expertise, carried out systematically and objectively through competency tests related to these professions/expertise that refer to national work competency standards, international standards, and/or other special standards. One way to get competency certification or professional certification is through a competency test or also known as competency assessment. The Government of Indonesia regulates the implementation of competency assessments as stated in Government Regulation (PP) No. 10 of 2018 which assigns the National Professional Certification Agency (BNSP) as an institution that ensures competency development in Indonesia. LSP Lingkungan Indonesia is a third party LSP (LSP-P3). Paperless is a policy in the reduction of paper in administrative activities and the transfer of information. The benefits are increasing productivity, cost-effectiveness, space efficiency and reducing environmental impact. Therefore, LSP Lingkungan Indonesia uses the Ourtoga website and assessees only need to bring a laptop, not having to bring a lot of documents when conducting an assessment. In this study using quantitative methods, descriptive methods, and causal methods aimed to determine the influence of ourtoga website-based green marketing on assessee interest. The result of this study is that ourtoga website-based marketing g reen has a significant influence on the interest of assessee at the Indonesian Environmental Professional Certification Institute with an influence contribution of 60.7%, meaning that the better understanding of website-based green marketing ourtoga will have an impact on the better interest of assessors at the Indonesian Environmental Professional Certification Institute.